Metabolic syndrome in chronic hepatitis C infection: does it still matter in the era of directly acting antiviral therapy? - Lim TR (Dove Medical Press, 2014)
TR Lim Centre for Liver Research and NIHR Biomedical Research Unit in Liver Disease, University of Birmingham and Liver and Hepatobiliary Unit, Queen Elizabeth Hospital Birmingham, UK Abstract: Metabolic syndrome is prevalent in patients with hepatitis C virus (HCV) infection. Given the pandemic spread of HCV infection and metabolic syndrome, the burden of their interaction is a major public health issue. The presence of metabolic syndrome accelerates the progression of liver disease in patients with HCV infection. New drug development in HCV has seen an unprecedented rise in the last year, which resulted in better efficacy, better tolerance, and a shorter treatment duration. This review describes the underlying mechanisms and clinical effects of metabolic syndrome in HCV infection, as well as their importance in the era of new directly acting antiviral therapy. Keywords: HCV, genotype 3, metabolic syndrome, steatosis, directly acting antiviral agents